Under (employability and financial) pressure: the unequal effects of work experience on graduate earnings - Luchinskaya, Daria; Tzanakou, Charikleia (Charoula) (Studies in higher education (Dorchester-on-Thames), 2025)
As students seek out work experience to become 'employable', many also do casual paid work while studying to ease financial pressures. But do different types of work experience affect graduates' earnings differently? We explore this question in this paper and discuss whether our findings are consistent with human capital or signalling theoretical perspectives. If human capital - any skill-developing work experience would increase earnings compared to doing nothing. If signalling - only certain (e.g. competitive) work experiences would improve earnings. We extend the work on the effect of placements on graduate earnings by Delis and Jones (2023) and respond to the authors' calls to analyse a larger UK sample by using rich, nationally representative survey data on students' higher education and post-graduation experiences (Futuretrack, N∼ = 3200). Using linear regression with extensive controls and sensitivity analysis, we demonstrate a hierarchy of work experience payoffs, with high, medium and low payoff groups, favouring internships and placements, career-related paid work, and casual paid work respectively. Career-related unpaid work shows no earnings advantages, and combining it with casual paid work may depress earnings, especially for female graduates. Our findings are therefore more consistent with the signalling, rather than the human capital, perspective. We further highlight that horizontal gender segregation in higher education subjects structures access to curricular work experience (sandwich and shorter placements) with differential earnings payoffs. We discuss the implications of our work for higher education institutions, careers professionals, employers and students regarding career information and access to work experience opportunities.